Insights into Primary Open-Angle Glaucoma Patients: Unveiling Demographic, Clinical, and Therapeutic Profiles in a Leading Tertiary Referral Hospital in Yogyakarta - Rizkah, Lailatul (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2024)
Introduction: Primary open-angle glaucoma (POAG) is the primary cause of irreversible blindness in adults worldwide. The characteristics of glaucoma patients and their response to therapy may differ by institution, region, and country. This study aimed to describe the demographic, clinical, and therapeutic aspects of POAG patients at Dr. Sardjito General Hospital Yogyakarta. Methods: This study included POAG patients who underwent full clinical ophthalmologic evaluations at Dr. Sardjito General Hospital Yogyakarta from January to December 2021. Characteristics such as age at presentation, sex, residence, visual acuity, intraocular pressure (IOP), cup-to-disc ratio (CDR), laterality of affected eyes, Humphrey field analyzer-measured mean deviation (MD), and pattern standard deviation (PSD), medical and surgical treatment were recorded retrospectively. Results: Data from 253 POAG patients were collected, the mean age was 52±17.15 years old and the female sex was more common at 58%. The mean IOP was 16.49±8.02 mmHg, and the mean CDR was 0.68±0.18. The mean refractive errors of all eyes were -0.64±0.22 dioptres (D), with 63% of eyes had good visual acuity (6/12 or better), 19% had moderate visual acuity (6/15 to 6/50), and 18% had poor visual acuity (count fingers to no light perception). Furthermore, the mean MD and PSD were -8.89±12.01 dB and 4.73±3.52 dB, respectively. Of all patients, 81% received medication only while 19% received medication and surgical intervention. Trabeculectomy was the most common surgery performed (94%). Conclusion: POAG is generally a bilateral disease and occurs mostly in middle age population. Overall, trabeculectomy was the most common surgery performed in POAG patients.